1980
DOI: 10.1182/blood.v56.6.1036.1036
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of glucocorticoid receptor studies in childhood acute lymphoblastic leukemia

Abstract: We have performed in parallel, in 19 children with acute lymphoblastic leukemia, a quantitative determination of glucocorticoid levels, in vitro steroid induced inhibition of nucleic acid precursors, and a short-term clinical trial of corticosteroids alone, before the treatment was given, which included corticosteroids and other drugs. From our results it appears that high glucocorticoid receptor levels in acute lymphoblastic leukemia of children do not guarantee a clinical response to corticosteroids. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…For a detailed summary of these studies, please refer to the review of Kaspers et al (1994a). Several authors studying the relationship between GR expression and clinical response to GCs or multiagent therapy found that a lower number of receptors per cell was associated with poor treatment response (Mastrangelo et al , 1980; Costlow et al , 1982; Pui et al , 1984; Quddus et al , 1985; Iacobelli et al , 1987), but this was not always confirmed (Homo et al , 1980). A large overlap between receptor expression in poor and good responders was observed (Quddus et al , 1985).…”
Section: The Glucocorticoid Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…For a detailed summary of these studies, please refer to the review of Kaspers et al (1994a). Several authors studying the relationship between GR expression and clinical response to GCs or multiagent therapy found that a lower number of receptors per cell was associated with poor treatment response (Mastrangelo et al , 1980; Costlow et al , 1982; Pui et al , 1984; Quddus et al , 1985; Iacobelli et al , 1987), but this was not always confirmed (Homo et al , 1980). A large overlap between receptor expression in poor and good responders was observed (Quddus et al , 1985).…”
Section: The Glucocorticoid Receptormentioning
confidence: 99%
“…A large overlap between receptor expression in poor and good responders was observed (Quddus et al , 1985). In addition, the cut‐off values of GR expression used in the different studies to define groups with poor and good prognosis varied considerably [from 4000 receptors/cell by Mastrangelo et al (1980) to 16 000/cell by Costlow et al (1982)]. With improvements in treatment protocols, the prognostic value of GR levels disappeared (Pui et al , 1984).…”
Section: The Glucocorticoid Receptormentioning
confidence: 99%
“…The finding that T-and B-ALL are relatively resistant to Pred correlates well with the fact that the number of glucocorticoid receptors are low in these phenotypes [17,18]. Low number of receptors usually implicate a Pred resistance but high numbers do not guarantee a response to this drug [19][20][21]. Therefore, studies to Pred resistance should incorporate a drug resistance assay, e.g., the MTT assay because this measures cell lysis which is the endpoint of all mechanisms of resistance instead of only the presence of receptors.…”
Section: Lmmunophenotype and Drug Resistancementioning
confidence: 95%
“…Small reductions in GR protein levels significantly affect GC response (Costlow et al, 1982;Gruber et al, 2009), thus the effect of GR expression levels on GC sensitivity has been extensively studied. While some studies report a correlation between quantitative expression of the GR and ligand binding on GC sensitivity (Mastrangelo et al, 1980;Marchetti et al, 1981;Pui et al, 1984;Tissing et al, 2005a), others do not confirm this association (Homo et al, 1980;Lauten et al, 2003a). However, it may be that a threshold GR level is needed for dexamethasone response and that higher levels confer no increased GC sensitivity.…”
Section: Mechanisms Of Dexamethasone Resistancementioning
confidence: 99%